Penerapan Pendekatan Konstekstual untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa pada Materi Operasi Hitung Campuran - Baiq Yuni Wahyuningsih (MANAZHIM, 2020)
This research is a Classroom Action Research with 2 (two) cycles which aims to improve students' creative thinking abilities through contextual approaches in mixed count operations material with qualitative approach. Data collection is done through observation, evaluation tools, interviews, documentation, and worksheets. The data analysis technique used in this study is descriptive qualitative Data triangulation is used to test the validity of the data. The data obtained came from three different sources, observers, teachers, and students. This research show most students become active gradually in learning activities. With a contextual approach students are motivated in finding meaning and concepts, observing, analyzing, determining completion strategies and alternatives to find the final result. An increase in students' creative thinking abilities in the aspects of fluency and flexibility from the pre-action stage to the end of the second cycle with a percentage of 25% to 60% (fluency) and 17.5% to 55% (flexibility).